Potential emotion recognition method based on knowledge guidance and generative adversarial learning - MA JUNHUI; NIU JIN; SONG JIANQIAO; JIA HAIRONG; WANG FEI; ZHAO CHENCHEN; XIANG CHENZHUO; XIANG HUSHENG; WANG FENG; SHI ZEZHOU (2020)
The invention discloses a potential emotion recognition method based on knowledge guidance and generative adversarial learning. The method mainly comprises the following steps of: 1, watching an induction video of a corresponding emotion for a subject so as to enable the subject to generate a corresponding potential emotion, using a Neuroscan Synamps2 electroencephalogram amplifier to collect EEGelectroencephalogram signals, and using a camera to collect facial expression video data to facilitate subsequent processing to obtain BVP pulse signals; 2, building a generative adversarial neural network model, and building a generator and a discriminator; and 3, performing discrimination by using the trained discriminator, and performing D-S decision fusion on discrimination results output by the two generative adversarial network discriminators to obtain a final result. The potential emotion recognition method based on knowledge guidance and generative adversarial learning has the advantages of being simple, effic